2009
DOI: 10.1016/j.childyouth.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

A review of services and interventions for runaway and homeless youth: Moving forward

Abstract: Research focused on the impact of community-based services and treatment interventions designed to intervene in the lives of runaway and homeless youth has increased in the last two decades in the U.S. and internationally. In light of the tremendous need for identifying effective strategies to end homelessness and its associated problems among youth, this paper summarizes and critiques the findings of the extant literature including U.S., international, and qualitative studies. Thirty-two papers met criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 69 publications
1
113
0
1
Order By: Relevance
“…However, the majority of research examines the relationship between a single provider and specific outcomes, primarily mental health issues, reductions in substance use, and psychosocial improvements Slesnick et al, 2009). No present studies have examined the correlation between number of service providers and perceptions of recovery, let alone from the perspectives of the homeless youth themselves.…”
Section: Service Provider Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of research examines the relationship between a single provider and specific outcomes, primarily mental health issues, reductions in substance use, and psychosocial improvements Slesnick et al, 2009). No present studies have examined the correlation between number of service providers and perceptions of recovery, let alone from the perspectives of the homeless youth themselves.…”
Section: Service Provider Networkmentioning
confidence: 99%
“…Service providers in the study included: health providers (doctor, nurse, or psychiatrist), housing workers, social workers, justice workers, probation officers, etc. All service providers were considered for the analysis as the recovery process for homeless youth must be multifaceted and involve interventions that extend across multiple domains of life (Slesnick et al, 2009;Palepu et al, 2012). Questions on the measure included: "In the past month, have you seen a health or social services provider at his or her office", "Who else have visited at their office this past month?…”
Section: Corrigan Et Al (2004) Also Conducted a Factor Analysis Of Tmentioning
confidence: 99%
“…Healthseeking beyond HIV/AIDS services has not been as thoroughly investigated; in fact, scholars who study international homeless adolescent populations call for increasing research to explore the factors that influence homeless youth's health-seeking behavior (Hudson et al, 2010;Raffaelli, 1999;Slesnick, Dashora, Letcher, Erdem, & Serovich, 2009). This lack of information about the health-seeking behavior of homeless youth extends to Vietnam, where there is a growing population of young people living on the streets (Ensign, 1998;Ensign & Gittelsohn, 1998;Hong & Ohno, 2005).…”
mentioning
confidence: 99%
“…For example, a person may feel personally discriminated against as a result of bureaucratic forms of authority and power relations structured by the service provision (Hoffman & Coffey, 2008). That is, if aspects of a service are deemed overly controlling or unfair -for example staff being overly strict in applying service rules and regulation -this may result in perceptions of discrimination (Heinze, Jozefowicz, & Toro, 2010;Slesnick et al, 2009). It is possible that the reverse of what we theorise is occurring, that is that low service identification leads to increased perceptions of discrimination.…”
Section: Perceived Discrimination and Identificationmentioning
confidence: 99%
“…There is evidence that these programs (that are more sensitive to the full range of factors that affect homeless individuals) are indeed achieving their aims (Black & Gronda, 2011;Zaretzky & Flatau, 2013). For example, longitudinal studies have found that when individuals make use of these support services, they have an increased likelihood of achieving outcomes such as obtaining stable housing, employment, and improvements in self-esteem (Lam & Rosencheck, 1999;Pollio, Thompson, Tobias, Reid, & Spitznagel, 2006;Slesnick, Dashora, Letcher, Erdem, & Serovich, 2009). …”
Section: A Tale Of Two Identities: Exploring the Predictors And Outcomentioning
confidence: 99%